Endoscopic Ultrasonography-Specific Stents - Shah, Rahul Haresh; Udawat, Priyanka; Dhir, Vinay (Journal of Digestive Endoscopy, 2021)
The evolution of the endoscopic ultrasonography (EUS) technique has necessitated the development of EUS-specific accessories and stents. In the earlier period, EUS-guided interventions mostly relied on borrowed accessories and stents from therapeutic endoscopy in particular ERCP. Traditional stents do not serve the purpose of EUS-guided transluminal stenting in all cases due to the length of the stent, no anchoring mechanism, and chance of migration. From 2011 onward, several EUS-specific stents became available, bringing a paradigm shift in interventional EUS. This article reviews current EUS-specific stents, indications, strengths, and weaknesses.
Keywords: BFMS; endoscopic ultrasound; LAMS